Leak : Why Mark Felt Became Deep Throat - Holland, Max (Book collections on Project MUSE., 2012)
This book reveals in detail what truly motivated Mark Felt, the FBI's number-two executive, to become the most fabled secret source in American history. The book showcases the many twists and turns to Felt's story that are not widely known, revealing not a selfless official acting out of altruistic patriotism, but rather a career bureaucrat with his own private agenda.